Measuring Workplace Spirituality Through Yoga : Implications for HR and Leadership - Joshi, Akashdeep; Kumar, Dinesh; Shabnam, (Prabandhan: Indian Journal of Management, 2025)
Purpose : The study developed and validated a scale to measure workplace spirituality in the Indian context, drawing upon the four classical paths of Yoga—Karma, Bhakti, Raja, and Jnana Yoga. Methodology : A mixed-methods approach, incorporating a literature review, expert insights, and quantitative analysis, was employed to design and validate the scale. The scale was validated using responses from 232 bank employees in the Delhi/NCR region. This study also investigated the impact of the scale on organizational commitment, work-life balance, and job satisfaction using SEM through AMOS 23. Findings : The scale demonstrated reliability, with Cronbach’s alpha values ranging from 0.933 to 0.837. Furthermore, confirmatory factor analysis conducted on the scale showed satisfactory results. SEM model testing revealed that Karma Yoga was the strongest predictor of outcome variables, explaining 59% of the variance in these variables, followed by Raja Yoga, which had a significant impact on all variables (41%). Bhakti Yoga was found to have a significant impact on both affective commitment and job satisfaction (5%), while Jnana Yoga was observed to have a significant negative effect on outcome variables (–16%). Practical Implications : The scale can help managers evaluate and support employees' spiritual well-being, particularly in the Indian context, leading to improved organizational performance and the cultivation of values-based leadership. Originality : By operationalizing different yoga paths, the study addressed a critical measurement gap and provided insights into workplace spirituality from an Indian perspective.